The Effect of Smartphone App-Use Patterns on the Performance of Professional Golfers - Lee, Jea Woog; Nam, Jae Jun; Kang, Kyung Doo; Han, Doug Hyun (Frontiers in Psychology, 2021)
Smartphone app-use patterns will predict professional golfers’ athletic performance, and the use time of serious apps would be associated with improved performance. This longitudinal 4-week observation of 79 professional golfers assessed golf handicaps and smartphone app-use patterns at the start of the Korean professional golf season and 2 and 4 weeks later. We classified use as social networking, entertainment, serious apps, and others. Use time of entertainment apps increased for non-improved golfers but did not change for improved golfers. Use time of serious apps increased for improved golfers and decreased for non-improved ones. Changes in golf handicaps were positively correlated with changes in entertainment app use time and negatively correlated with changes in serious app use time. Professional golfers’ sports performance was not associated with smartphone use time but was with the smartphone app type. The management of smartphone app-use patterns is important for professional golfers’ performance.